Implementation of ISO Frameworks to Risk Management in IPv6 Security - Opuda, John (My University, 2023)
The Internet of Things is a technology wave sweeping across various industries and sectors. It promises to improve productivity and efficiency by providing new services and data to users. However, the full potential of this technology is still not realized due to the transition to IPv6 as a backbone. Despite the security assurances that IPv6 provides, privacy and concerns about the Internet of Things remain. This is why it is important that organizations thoroughly understand the protocol and its migration to ensure that they are equipped to take advantage of its many benefits. Due to the lack of available IPv4 addresses, organizations are in an uncertain situation when it comes to implementing IoT technologies. The other aim is to fill in the gaps left by the ISO to identify and classify the risks that are not yet apparent. The thesis seeks to establish and implement the use of ISO to manage risks. It will also help to align security efforts with organizational goals. The proposed solution is evaluated through a survey that is designed to gather feedback from various levels of security and risk management professionals. The suggested modifications are also included in the study. A survey on the implementation of ISO frameworks to risk management in IPv6 was conducted and with results as shown in the random sampling technique that was used for conducting the research a total of 75 questionnaires were shared online, 50 respondents returned responses online through emails and social media platforms. The result of the analysis shows that system admin has the highest pooling 26% of all the overall participants, followed by network admin with 20%, then cybersecurity specialists with 16%. 14% of the respondents were network architects while senior management and risk management professionals were 4% and 2% respectively. The majority of the respondents agreed that risk treatment enhances the risk management performance of the IPv6 network resulting from the proper selection and implementation of correct risk prevention strategies.
Keywords: IPv6 Security, Internet of Things, Risk Management,ISO